Capacitive measuring of crude palm oil-water mixture - Sriphant, Pongsakun; Srongprapa, Anupong; Klongratog, Bhanupol (My University, 2017)
Oil palm is one of the famous commercial crops of Thailand. The production is in the 3th rank of the south east Asia, and plantation is still increasing every year. To investigate the feasibility of using electrical capacitance measuring technique as an alternative method for low-cost non-destructive, oil palm fresh oil (CPO) and water have been prepared and studied. One group is concerned with the immiscible fluid and another is all ultrasonic shakes. The mass concentration (x) of CPO varied from 0 g/cm3 to 0.9 g/cm3 and then all experiments were tested on room temperature (25oC). Guard parallel structure has been used in conjunction with AD7747 capacitive to digital converter to obtain capacitance value (y). The results show that y = 0.11987x2 - 0.46104x + 0.47418 with r2 = 0.98098. The model for second sample is y = 0.08965x2 - 0.41335x + 0.3731 with r2 = 0.9554. The capacitance of first sample is higher than the second sample. As previously mentioned, this project aims to make benefit of interest on seasonable optimistic harvests.
Keywords: Capacitive sensing; Crude palm oil (CPO); Non-Destructive; Ripeness; Ultrasonic